ANALISIS PENGARUH DARI MEKANISME CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA - ARYA PRADIPTA (Jurnal Bisnis dan Akuntansi, 2011)
The research aims to see the impact of corporate governance mechanisms which consist of institutional ownership variables, managerial ownership variables, the number of board of directors variables and audit committee variables in accordance with the regulation of Jakarta Stock Exchange (JSE) on earnings management. A statistical technique used in this study is a statistical technique of multiple regressions. The sample that companies used in this study are registered companies in the Jakarta Stock Exchange in 2004 and did not belong to the period of industrial enterprises of agriculture, mining, property, transportation, finance, services and construction. The results showed that the mechanism of corporate governance that consists of variable institutional ownership, managerial ownership variables, and the audit committee variables in accordance with the regulation of the Jakarta Stock Exchange (JSE), have no significant effect on earnings management. On the other hand, the corporate governance mechanism which represented by the board of directors variables has a significant influence to earnings management.